Microwave Thermotherapy: New treatment for cutaneous leishmaniasis - Khalifa E. Sharquie; Sabeeh A. Al-Mashhadani; Adil A. Noaimi; Wasan B. Al-Zoubaidi (Our Dermatology Online, 2015)
Introduction: Cutaneous leishmaniasis(CL) is an endemic disease with variable therapeutic agents. Microwave radiation has been used in many medical disciplines as therapeutic and diagnostic tools. Objective: To evaluate the efficacy of microwave radiofrequency in the treatment of cutaneous leishmaniasis. Patients and methods: This is a case, controlled, therapeutic, clinical trial. Thirty five patients completed the study, 18 (51.43%) females and 17 (48.57%) males, with female to male ratio 1.1:1, their ages ranged from 6-60 (26.98±15.22) years and the duration of lesions ranged between 1-6 (2.17±1.44) months. The size of lesions ranged from 1-6.5 (2.87±1.60) cm. Eleven (31.43%) patients had single lesion and 24 (68.57%) patients had multiple lesions. Classical cases of CL were studied and diagnosis was confirmed by histopathological examination. Lesions had been divided in 2 groups, Group A: lesions were exposed to a microwave radiation once every two weeks for a maximum of 8 weeks, while Group B lesions, received no treatment and left as a control group. Patients were seen every 2 weeks for 8 weeks to reassess the therapeutic effect and to record any side effects. Follow up after cure was carried out for 2-6 months to watch any sign of relapse. Results: The total number of lesions were 99;52 (52.53%) ulcerated lesions and 47 (47.47%) dry lesions. In Group A, 64 (85.33%) lesions out of 75 showed clinical cure with 1-4 (2.77±0.91) sessions while in Group B, 5 (20.83%) lesions out of 24 lesions showed slight healing during the treatment period. No side effects appear in all patients. Conclusion: Microwave thermotherapy is highly effective, new therapy for cutaneous leishmaniasis with no harmful side effects.